Nitric oxide-releasing S-nitrosothiol-modified silica/chitosan core–shell nanoparticles. (28th January 2015) - Chang, Wei-Lin; Peng, Kang-Jen; Hu, Teh-Min; Chiu, Shih-Jiuan; Liu, Ying-Ling
Abstract: Nitric oxide-releasing core–shell nanoparticles possessing silica cores and S-nitrosothiol-modified chitosan shells have been prepared. The S-nitroso groups are incorporated to the thiol-modified chitosan shell layers of the nanoparticles. The synthesis route involves two major reactions of (a) incorporation of chitosan chains to silica nanoparticles and (b) thiolation of chitosan chains. The sample made with the synthesis route which performs first theb reaction shows a higher NO-releasing amount than does the analogue prepared with the a-reaction-first synthesis route. The chemical structures and morphology of the nanoparticles have been characterized with spectral methods and electronic microscopies. The prepared sample shows a NO-releasing amount of 0.15 μmol SNO group/mg with a prolonged NO release. Graphical abstract: Highlights: Silica@chitosan core–shell NO-releasing nanoparticles are prepared. Two synthesis routes are developed for comparison. The nanoparticles show a prolonged NO release property. The first example of organic–inorganic nanohybrids for NO-releasing.